Antiproliferative Activity of Ethanolic Extract of Ciplukan Herbs (Physalis angulata L.) on 7,12-Dimethylbenz[a]nthracene-Induced Rat Mammary Carcinogenesis - Monikawati, Ameilinda; Farida, Sofa; Putri, Laras Widawaty; Ikhtiarsyah, Yurista Gilang; Meiyanto, Edy (Indonesian Research Gateway, 2011)
Physalis angulataÃÂ L.ÃÂ isÃÂ anÃÂ annualÃÂ herbÃÂ widelyÃÂ usedÃÂ asÃÂ popularÃÂ medicineÃÂ forÃÂ the treatment of cancer. Physalis angulata L. ethanolic extract (PEE) has been demonstrated to have strong cytotoxic activity against breast cancer, inhibited cancer cellÃ¢â¬â¢s proliferation and inducedÃÂ cellÃÂ cycleÃÂ arrest.ÃÂ TheÃÂ aimÃÂ ofÃÂ ourÃÂ studyÃÂ isÃÂ toÃÂ investigateÃÂ theÃÂ effectÃÂ ofÃÂ PEEÃÂ asÃÂ a cancerÃÂ chemopreventiveÃÂ agentÃÂ onÃÂ 7,12-dimethylbenz[a]nthraceneÃÂ (DMBA)-inducedÃÂ rats mammary. The antiproliferative activity was characterized by monitoring the histopatology representationÃÂ andÃÂ expressionÃÂ ofÃÂ cellÃÂ proliferationÃÂ onÃÂ DMBA-inducedÃÂ mammaryÃÂ ratsÃÂ that wereÃÂ treatedÃÂ withÃÂ PEEÃÂ againstÃÂ controlÃÂ groups.ÃÂ TheÃÂ histopatologyÃÂ representationÃÂ were analyzedÃÂ byÃÂ HaematoksilinÃÂ EosinÃÂ (HE)ÃÂ stainingÃÂ method,ÃÂ whileÃÂ proliferativeÃÂ activityÃÂ was detected by AgNOR method. The HE staining results showed significant differences in cells morphologyÃÂ ofÃÂ treatmentÃÂ groupsÃÂ comparedÃÂ toÃÂ theÃÂ controlÃÂ groups.ÃÂ ThusÃÂ resultsÃÂ suggest thatÃÂ PEEÃÂ wasÃÂ ableÃÂ toÃÂ repairÃÂ morphologyÃÂ ofÃÂ cellsÃÂ undergoingÃÂ carcinogenesis.ÃÂ AgNOR methodÃÂ showedÃÂ decreasingÃÂ occurrenceÃÂ ofÃÂ blackÃÂ dotsÃÂ betweenÃÂ treatmentÃÂ andÃÂ control groups. Thus, we conclude that PEE has an antiproliferative activity on DMBA-induced rat mammary.ÃÂ Therefore,ÃÂ theÃÂ ethanolicÃÂ extractÃÂ ofÃÂ PhysalisÃÂ angulataÃÂ herbsÃÂ isÃÂ aÃÂ potential chemopreventive agent on cancer. Further study on its molecular mechanism needs to be explored. Keywords:ÃÂ PhysalisÃÂ angulata,ÃÂ breastÃÂ cancer, 7,12-dimethylbenz[a]nthracene, carcinogenesis, antiproliferative